Environmental justice and park accessibility in urban China: Evidence from Shanghai. (13th July 2021) - Wang, Chunlan; Li, Chen; Wang, Mark; Yang, Shangguang; Wang, Luyao
Abstract : This article applies the pluralistic concept of environmental justice to the issue of park accessibility between people across different socioeconomic strata in the metropolitan region of Shanghai. Data were obtained from China's 2000 and 2010 population census, Shanghai Landscaping and City Appearance Administrative Bureau, semi‐structured interviews and secondary sources. The article finds significant environmental injustice between foreign citizens and Chinese citizens (including people from Hong Kong, Macau and Taiwan and mainland people with and without Shanghai hukou ) and between blue collar, white collar and wealthy white collar people from distributive, recognition, participatory and procedural justice perspectives. The article then discusses why such injustice is the result of urban China's unique authoritarian mode of governance, power structure, neoliberal practice and globalisation development. The findings offer insights into the development of the concept of environmental justice in the Chinese context and the country's objective to build an impartial society.